Participatory rangeland mangement: Virtual presentation made to members of the World Bank Horn of Africa team and ministry partners - Flintan, Fiona E. (International Livestock Research Institute, 2024)
Virtual presentation made to members of the World Bank Horn of Africa team and ministry partners supporting the implementation of the Ground Water for Resilience Project and the Somalia Barwaaqo project